SEVERITY INDEX IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - N. G. Klyukvina; E. A. Aseeva; G. V. Lomanova; E. A. Vedernikova (Научно-практическая ревматология)
Objective: to assess the clinical and prognostic informative values of SI in patients with SLE.Subjects and methods. One hundred and forty-six male patients aged 15 to 64 years with a valid diagnosis of SLE who had been followed up for 15 years were assessed. The patients underwent conventional clinical, laboratory, and instrumental investigations using the standard methods of disease activity assessment. SI and SLICC/ACR Damage Index (SDI) were used to characterize the course and outcomes of SLE. The SI and SDI were analyzed in 133, 91, and 63 patients over time at 1, 5, and 10 years of the disease, respectively.Results. Significant correlations were found between the SI on study inclusion and the indices reflecting the course and activity of SLE. Analysis of changes in SLE indicated that its maximum increase during the first 5 years of the disease was observed in patients aged < 20 years at the onset of SLE. The patients who had SLE concurrent with secondaryantiphospholipid syndrome showed a more marked SI rise than those without these abnormalities. The highest survival rates were noted in patients with an early SI of 0.Conclusion. SI is a good indicator reflecting the accumulated activity of the disease. It increases with longer disease duration; moreover, its rise may occur at any disease stages. This trend depends on the form of the disease, the time of diagnosis, and the presence of comorbidity. SI correlates well with the activity and damage indices traditionally used in SLE and with the frequency of exacerbations, suggesting that SI may be used as a prognostic marker.